Hospital discharge documentation and risk of rehospitalisation. Issue 9 (22nd April 2011) - Hansen, Luke O; Strater, Amy; Smith, Lisa; Lee, Jungwha; Press, Robert; Ward, Norman; Weigelt, John A; Boling, Peter; Williams, Mark V
Abstract : Background: Avoidable hospital readmission is a focus of quality improvement efforts. The effectiveness of individual elements of the standard discharge process in reducing rehospitalisation is unknown. Methods: The authors conducted a case-control study of 1039 patients experiencing rehospitalisation within 30 days of discharge and 981 non-rehospitalised patients matched on admission diagnosis, discharge disposition, and severity of illness. In separate models for each discharge process component, the authors measured the relationship between readmission and discharge summary completion, contents of discharge summary, completion of discharge instructions, contents of discharge instructions, presence of caregiver for discharge instruction, completion of medication reconciliation, and arrangement of ambulatory follow-up prior to discharge. Results: Adjusting for patient and hospital characteristics, including severity of illness and discharge disposition, the study failed to find an association between readmission and most components of the discharge process. There was no association between readmission and medication reconciliation, transmission of discharge summary to an outpatient physician, or documentation of any specific aspect of discharge instruction. Associations were found between readmission and discharge with followup arranged (adjusted odds ratio (OR) 1.21; 95% CI 1.05 to 1.37) and increasing number of medicines (adjusted OR 1.02; 95% CI 1.01 to 1.04). Conclusions: Documentation of discharge process components in the medical record may not reflect actual discharge process activities. Alternatively, mandated discharge processes are ineffective in preventing readmission. The observed absence of an association between discharge documentation and readmission indicates that discharge quality improvement initiatives should target metrics of discharge process quality beyond improving rates of documentation.